The differentiation and management of inflammatory bowel disease - Mokrowiecka, Anna; Małecka-Panas, Ewa (Przewodnik Lekarza/Guide for GPs, 2007)
Despite the progress in our knowledge of inflammatory bowel disease immunology and genetic pathways, there is still a lack of a single gold standard and diagnosis is based on clinical, radiographic and endoscopic methods with histopathological assessment. Even when combining all available conventional diagnostic methods the exact diagnosis still remains inconclusive and these cases are classified as indeterminate colitis. Several serologic methods are under evaluation due to their diagnostic usefulness. The newest therapies targeting various levels of immunologic processes have been recently developed, particularly those connected with tumour necrosis factor alpha.